PENGARUH DEFLECTOR CHUTE CV. 501 A MENJADI SIZING SCREEN UNTUK PENGOPTIMALAN KINERJA QUADROL CRUSHER DIJALUR UNLOADING SISTEM RCD 3 DI SATUAN KERJA OPERASI PT. BUKIT ASAM TBK, (STUDI KASUS UNIT PELABUHAN TARAHAN) - Daud Irawan; Burhan Nudin (Industrika : Jurnal Ilmiah Teknik Industri, 2020)
This research is motivated by the problems faced by PT.Bukit Asam Tbk. which is constrained by a decrease in productivity on the unloading path of the RCD 3 system, precisely in the quadrol crusher unit.The purpose of this study is to improve the capacity of the quadrol crusher by modifying the cv 501 a chute declector unit into a sizing screen (coal separator unit) so that the loading rate can be obtained in the design capacity. And the methodology used in this study is a fishbone method and pareto chart. Based on the results of research conducted using the fishbone method and pareto chart, it is known that the most dominant factors causing the decreasing working capacity of the rcd 3 unloading path are method and machine factors. And the conclusion of this research exhibited the fishbone method and pareto chart is by only modifying the cv 501 a chute deflector into a sizing screen that only costs a small modification, then PT. Bukit Asam Tbk will get the opportunity to re-optimize the rcd 3 unloading path near capacity design in order to increase profits for the company